Passive leg raising test – optimal methodology. A systematic review and meta-analysis (literature review) - L. B. Berikashvili; I. V. Kuznetsov; P. A. Polyakov; M. Ya. Yadgarov; P. V. Ryzhkov; A. A. Yakovlev; E. M. Korolenok; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии)
Introduction. The passive leg raising (PLR test) test is a widely used diagnostic test for assessing fluid responsiveness. However, there is no generally accepted methodology describing the details of its implementation.The objective was to establish criteria for conducting the PLR test based on the diagnostic accuracy of various variations.Materials and methods. A systematic review and meta-analysis included prospective cohort studies that evaluated the diagnostic accuracy of different PLR test variations. The primary endpoint was the area under the ROC curve (AUROC). The search was conducted up to March 2024 and included «snowball» method. The covariate influence was assessed via univariate meta-regression. The risk of bias was evaluated using QUADAS-2, and evidence certainty was assessed with GRADE.Results. The meta-analysis included 33 prospective cohort studies, 1,607 critically ill patients The AUROC for the PLR test was 0.882 [0.849; 0.916] (moderate certainty of evidence). Transthoracic and transesophageal echocardiography, transpulmonary thermodilution, and pulse contour analysis showed comparable results for assessing cardiac hemodynamics during PLR test, p = 0.253 (moderate certainty of evidence). Evaluating hemodynamic changes within the first two minutes of the PLR test increased diagnostic accuracy (high certainty of evidence). The starting body position (low Fowler’s position or supine) during the PLR test did not impact diagnostic accuracy (low certainty of evidence). Baseline covariates (age and gender) had no effect on diagnostic accuracy of the PLR test in critically ill patients (high certainty of evidence).Conclusion. For assessing fluid responsiveness in critically ill patients, the PLR test should include intracardiac hemodynamic assessment within two minutes using any common method. Low Fowler’s position is preferable starting position of the body for PLR test.